Christian Leadership Management: Building Christ-Centered Leaders - Merianti Atakameng (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
This article discusses the concept of Christian leadership management centered on Christ as the foundation for forming spiritual leaders who are characterized by integrity and service. In today’s modern context, which is often driven by power orientation and human-centered success, Christian leadership offers an alternative paradigm rooted in love, humility, and servanthood. Through a literature review of various thinkers such as Daniel Ronda, Yohanes Nuban Timo, Hendrik Senduk, and John C. Maxwell, this paper emphasizes that the essence of Christian leadership is not position but a calling to serve and to make disciples of Christ. Christian leadership management encompasses theological, spiritual, and practical dimensions, ranging from personal transformation, spiritual discipline, and the formation of Christlike character, to ministry management based on servant leadership principles. This article also integrates relevant secular leadership theories such as servant leadership, transformational leadership, and situational leadership with biblical values. In conclusion, effective Christian leadership can only be realized when leaders follow the example of Christ, depend on God’s wisdom, and produce new leaders who are able to bring spiritual and social impact to the world.